2021
DOI: 10.1038/s41598-021-98705-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing effectiveness of Komagataeibacter strains for producing surface-microstructured cellulose via guided assembly-based biolithography

Abstract: In this study, a medical device made of surface microstructured bacterial cellulose was produced using cellulose-producing acetic acid bacteria wild-type strains in combination with guided assembly-based biolithography. The medical device aims at interfering with the cell's focal adhesion establishment and maturation around implantable devices placed in soft tissues by the symmetrical array on its surface. A total of 25 Komagataeibacter strains was evaluated over a three-step selection. In the first step, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The variation in these results confirmed that BC production efficiency is strain dependent and closely related to the carbon source preference of the particular strain [ 31 ]. The role of intra-species variability in the effectiveness of synthesis of various biological-derived products, including BC, has been broadly discussed in the relevant literature [ 39 , 40 , 41 , 42 ]. Therefore, to enable replication and comparison with similar experiments by other research teams, we deliberately focused on the ATCC reference strains of K. xylinus .…”
Section: Resultsmentioning
confidence: 99%
“…The variation in these results confirmed that BC production efficiency is strain dependent and closely related to the carbon source preference of the particular strain [ 31 ]. The role of intra-species variability in the effectiveness of synthesis of various biological-derived products, including BC, has been broadly discussed in the relevant literature [ 39 , 40 , 41 , 42 ]. Therefore, to enable replication and comparison with similar experiments by other research teams, we deliberately focused on the ATCC reference strains of K. xylinus .…”
Section: Resultsmentioning
confidence: 99%
“…The hierarchical polymerization of the glucan chains confers to BC unique properties, such as high crystallinity and high tensile strength ( Singhania et al, 2021 ). Such properties make BC suitable for a wide range of applications, spanning from food ( Vigentini et al, 2019 ), biomedical ( Brugnoli et al, 2021 ; Manan et al, 2022 ) and cosmetics fields ( Ullah et al, 2015 ). The most performant BC producers are found within the Acetobacteraceae family.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned species were described to achieve variable and considerable BC yield and be able to metabolize different carbon sources for BC production ( Masaoka et al, 1993 ; Keshk and Sameshima, 2005 ). Among the described species of Komagataeibacter, high intra and inter-species variability in term of BC yield was observed ( Brugnoli et al, 2021 ; La China et al, 2021 ). However, K. xylinus species is considered as the model organism for BC production and the highest producer in different conditions ( Wang et al, 2018 ; Zhong, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial cellulose (BC), one of the most abundant natural biopolymers, is synthesized by some cellulose-producing bacteria such as those in the genera of Komagateibacter, Gluconacetobacter, Agrobacterium, Achromobacter, Aerobacter, Azotobacter, Sarcina ventriculi, Salmonella, Escherichia, and Rhizobium, as extracellular cellulose brils and can be used as a promising renewable resource or an eco-friendly alternative to petroleum-based products (Wan et al 2009; Chen et al 2017). Komagateibacter sucrofermentans, Komagateibacter xylinus and Komagateibacter hansenii were reported as the most common and highest BC producers among the acetic bacteria species of the Komagataeibacter genus (Sheykhnazari et al 2011;Brugnoli et al 2021; Vilela and Freire 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As recorded in Table1, the BCL yield obtained by the effect of the Considering the above descending order, the highest BC yield rate was obtained during the rst 2 days of bacterial cultivation, reaching out the 40-45% per day, while the lowest BC yield rate of 6% was obtained during the 2nd -3rd day.Comparing to previous studies about BC yields by Komagataeibacter strains, Brugnoli et al, added 5% (v/v) inoculum of the same strain of K. sucrofermentans (DSM 15973 T ) in HS medium with static cultivation mode at 28°C, giving a maximum BC yield of 0.81 g dried/L(Brugnoli et al 2021), while in our study, 20% (v/v) inoculum of the bacterium was used in HS medium with static cultivation mode at 30°C, giving a maximum BC yield of 4.67 g freeze-dried/L after 7 days. In the study of Chen et al(Chen et al 2017), 10% (v/v) of different K. sucrofermentans strains (ATCC 700178, ATCC 10245, ATCC 23769, KTH 5655, NBRC 13693, ATCC 53524) were used in HS medium with static cultivation mode at 30°C, giving various BC yields of 1.90-10.39 g dried/L after 9 days.…”
mentioning
confidence: 99%